Experiential Learning at Universities and its Benefits for Students and Teaching Faculty - Gleason Rodríguez, Miriam A. (2020)
Given society´s demand for educational transformation, universities are now reconsidering their focus and modifying their educational strategies. One strategy that universities are now embracing includes experiential learning. A review of both documentation published by universities on their websites and relevant research articles was conducted to understand how universities perceive and apply experiential learning. The conclusion denotes that universities are currently adding experiential learning to their educational models by involving their students in real-life projects. As a result, students have greater insight into community issues and have developed important skills for the 21st century such as creativity, communication, collaboration and critical thinking. The role of the teaching faculty has also evolved and is essential for educational innovation to be successful.